SENSITIVITY APPROACH OF OPTICAL SENSORS OF CHOLESTEROL DETECTION THROUGH GAUSSIAN BEAM AND QUASI-GAUSSIAN BEAM - Budiyanto, Mohammad; Yasin, Mohamad; Harun, Sulaiman Wadi (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2019)
Sensitivity is the comparison result between changes in output signal intensity and changes in input signal shift sensor. The purpose of this study was to analyze the sensitivity of fiber optic sensors using mathematical analysis through the Gaussian beam approach and quasi-Gaussian beam compared with the sensitivity of the optical sensor experimental results so that it can find the correct approach of sensitivity values between theory and experiment. The research method used mathematical analysis and experimental methods and mathematical descriptions for the description of the bundle optical fiber used in the experiment until the sensitivity equation is obtained. The results of the mathematical analysis of the Gaussian beam sensitivity values obtained of S = 0.004 mV ppm-1 and the sensitivity of quasi-Gaussian beam of S = 0.08 mV ppm-1. The results of the sensitivity of experimentally obtained S = 0.11 mV ppm-1. Based on the results of mathematical, experimental analysis, and sensor performance, sensitivity through the flat mirror reflection field, it can be concluded that the sensitivity of the optical fiber sensor tends to approach through the quasi-Gaussian beam approach to determine cholesterol concentration.